Leader-member exchange, emotional intelligence and disabled employees’ job embeddedness: the mediating role of organizational climate / Hasnizawati Hashim - Hashim, Hasnizawati (Institute of Graduate Studies, UiTM, 2017)
The foundation of this research is that disabled employees will engage with their job if they receive support from each of the important elements in the workplace. There are many researches that focused on investigating various outcomes of job embeddedness but little is known on what makes PWD stay with their job. Understanding job embeddedness among person with disabilities is very crucial as it focuses on the factors that may influence their job retention. Hence, the Unfolding Model in this study provides basic understanding on the relationships between variables that makes people embedded to their job. Furthermore, Social Cognitive Theory is applied according to the justification that individual behaviour could be explained through a self-regulatory system. This system explains that individuals are believed to have control over their own thoughts and behaviour. This system will be operated if it is activated by the person. So, job embeddedness is the construct that describes the activation or deactivation of an individual’s self-regulatory system. This research investigates specifically, (1) direct relationship between leadermember exchange, emotional intelligence, organizational climate and job embeddedness, 2) direct relationship between leader-member exchange, emotional intelligence and organizational climate, and 3) organizational climate mediation relationship between a) leader-member exchange, b) emotional intelligence and job embeddedness among disabled employees in Malaysia by applying The Unfolding Model, Social Cognitive Theory and supported by the Person-Environment Fit Theory. A two-stage sampling technique was applied to randomly collect data from disabled employees in private and public sectors at the operational level in Malaysia.